Differences of Increased Bishop Scores Between Neutrophil Swab Vaginal ≤ 5 and > 5 in 41 Weeks of Pregnancy Induced With Misoprostol - Boby Hartanto; Joserizal Serudji; Defrin Defrin (Universitas Andalas, 2021)
The incidence of labor induction with various indications was to increase. The key to successful labor induction is a ripe cervix. Research shows that the degree of cervical rippening as assessed by the Bishop score is influenced by the level of neutrophils contained in the cervical stroma which can be detected by performing a vaginal swab. Neutrophils will produce collagenase in the form of matrix metalloproteinase - 8 (MMPs - 8) which will degrade cervical collagen fibers, so that the cervix becomes soft and ripe. Misoprostol is the drug most widely used in labor induction today. Purpose: This study was to determine the difference in Bishop score increase between vaginal swab neutrophils ≤ 5 and > 5 in pregnancy ≥ 41 weeks induced by misoprostol.Keywords: Bishop score, neutrophil, vaginal swab, misoprostol